Introduction: Governing Emergencies: Beyond Exceptionality. (March 2015) - Adey, Peter; Anderson, Ben; Graham, Stephen
What characterizes emergency today is the proliferation of the term. Any event or situation supposedly has the potential to become an emergency. Emergencies may happen anywhere and at any time. They are not contained within one functional sector or one domain of life. The substantive focus of the articles collected in this special issue reflects this proliferation: they explore ways of governing in, by and through emergencies across different types of emergencies and different domains of life. In response to this proliferation, the issue opens up critical work on the politics of emergency beyond the 'state of exception' as dominant paradigm. Emergency is treated as a problem for government that calls for the invention of new techniques or the redeployment of existing techniques. Through this shift in emphasis, the articles in this issue disclose relations between modalities of power and emergency life that differ from the 'lightening flash' of a sovereign decision on the exception taken from outside of life, or the capacity to 'mould' an always-already emergent life from within life.